MARKETING STRATEGY OF SHREDDED CHILI PRODUCTS PT EVIA MAJU BERSAMA, BOGOR, WEST JAVA - Mudatsir Najamuddin; Rizki Adi Puspita Sari; Anindya Kariza (Syarif Hidayatullah State Islamic University Jakarta, 2021)
This research is backgrounded by the processing of chili as an alternative to extending the shelf life of chili and PT. Evia Maju Bersama is one of the businesses engaged in the production and trade of processed chili into shredded chili. Until now, the company continues to strive to market its products even though there are several obstacles faced, such as promotional activities carried out not running well, experiencing a decrease in sales due to lifestyle changes, competition with similar companies and the income received did not reach the target. Based on these problems, this study aims to, 1) identify internal and external factors that affect the marketing of PT Evia Maju Bersama, 2) find out the position of PT Evia Maju Bersama based on internal and external factors, 3) Develop alternative product marketing strategies that can be applied, and 4) determine the priorities of marketing strategies that are in accordance with PT Evia Maju Bersama.The results of this study found that based on the IFE matrix, 6 strengths and 6 weaknesses could be identified with a total score of 2,843 for internal factors and 2,997 for external factors. The total score results on the IFE and EFE matrices positioned in the IE matrix on cell V belong to the category of held and guarded positions. The SWOT matrix produces 5 alternative marketing strategies that companies can apply. The results of the QSPM matrix analysis show that the strategies that are the top priority to be implemented are carrying out product promotion activities through social media and marketplaces, and building a brand image through personal selling, direct marketing, and online promotion.